2011
DOI: 10.1038/leu.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Early recipient chimerism testing in the T- and NK-cell lineages for risk assessment of graft rejection in pediatric patients undergoing allogeneic stem cell transplantation

Abstract: Timely diagnosis of impending graft rejection is crucial for effective therapeutic intervention after allogeneic hematopoietic stem cell transplantation (SCT). We have investigated the predictive potential of early leukocyte subset-specific chimerism for graft loss in children undergoing SCT. In total, 192 pediatric patients transplanted for the treatment of malignant and non-malignant diseases after reduced-intensity or myeloablative conditioning were investigated. Surveillance of lineage-specific chimerism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…1,4,23 When rare cell subsets are isolated for subsequent chimerism analysis, the availability of sufficient amounts of DNA may become a limiting factor with regard to the achievable sensitivity and reproducibility of results. The experience among members of the EUC consortium indicated that the cell number available for analysis in these instances can be as low as a few hundred to a few thousand cells.…”
Section: Resultsmentioning
confidence: 99%
“…1,4,23 When rare cell subsets are isolated for subsequent chimerism analysis, the availability of sufficient amounts of DNA may become a limiting factor with regard to the achievable sensitivity and reproducibility of results. The experience among members of the EUC consortium indicated that the cell number available for analysis in these instances can be as low as a few hundred to a few thousand cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that the assessment of lineage-specific chimerism within the first weeks after allogeneic HSCT facilitates prediction of the risk of graft rejection in transplant recipients, including children with ALL. 13 In the present prospective multicenter study performed in a large cohort of pediatric patients with highrisk ALL over a period of 10 years, we have addressed the possibility of exploiting lineage-specific monitoring of chimerism for timely assessment of the risk of relapse after allogeneic HSCT. The study was performed in a blinded fashion to prevent the lineage-specific chimerism test results from having any influence on clinical decisions.…”
Section: Risk Assessment Of Relapse By Lineage-specific Monitoring Ofmentioning
confidence: 99%
“…BM chimerism on day þ 30 of these cases showed a median of 100% of CB cells (range 75-100%). Median time to neutrophil engraftment in this group was 19 days (range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Standard Engraftment Group (N ¼ 14)mentioning
confidence: 99%
“…[19][20][21][22] This is especially true if chimerism is analyzed in different cell subsets. 23 More recently, chimerism studies performed on CD3 þ cells after double CB transplantation with reduced intensity conditioning have been shown to predict unit dominance. 24 The aim of this study was to analyze the early post-transplant (first 30 days) chimerism dynamics in peripheral blood (PB) and T cells after dual SCT in order to predict CB engraftment after dual SCT.…”
Section: Introductionmentioning
confidence: 99%